Analysis Of Tech Addiction Among Students Of Different Domains (Journal of Namibian Studies : History Politics Culture, 2023)
This research investigates tech addiction among students across diverse academic domains, employing a mixed-methods approach to discern prevalence, patterns, and contributing factors. By surveying and interviewing students in fields such as science, engineering, humanities, and social sciences, the study aims to identify discipline-specific tech usage trends and dependencies. The research explores the impact of tech addiction on academic performance and mental well-being while seeking to uncover nuanced insights into the unique challenges faced by students in different fields. The findings will inform targeted interventions and strategies to address tech addiction, fostering a comprehensive understanding of the interplay between technology and student well-being in the digital age.